THE ROLE OF THE USE OF DIGITAL E-WALLET FINANCIAL TRANSACTION PAYMENTS FOR UMKM IN THE EAST MEDAN REGION - Adha, Wahyuni; Annisa Salwa, Alya; Azhara siregar, Putriyani; Sabila Hawani, Yasmine; Hayati, Isra (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine the role of using e-wallets in digital financial payment transactions for MSMEs, as well as the obstacles experienced by MSMEs in using e-wallets as a means of payment in digital financial transactions. This research uses qualitative methods by conducting a survey of MSME owners who use e-wallet in the East Medan District area. The research results show that the use of e-wallets for MSMEs has increased payment accessibility, expanded the market, and increased operational efficiency. Some examples of e-wallets used by MSMEs are OVO, dana, sakuku, and linkAja. Thus, the use of e-wallets has an important role in strengthening the MSME ecosystem, providing greater growth opportunities, and empowering MSMEs to compete in a global market that is increasingly connected digitally. However, there are also several obstacles in using e-wallets in MSME financial payment transactions, such as system errors which result in delays in payment transactions. It is hoped that the results of this research can contribute to MSMEs in using e-wallets as a digital financial payment transaction tool.